DIFFERENT PERCEPTIONS ABOUT TOURIST IDENTITY IN THE DANUBE GATE DESTINATION - SABINA GHEORGHECI; MIRELA MAZILU (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2015)
Thus, uncontrollable elements such as nice weather, nature/scenery, accessibility, transformed into controllable elements such as pleasant environment, relaxing atmosphere, infrastructure, can create a favourable artistic image that would determine the tourist to pick the destination. Uncontrollable elements such as local culture, diversity of sport activities, of restaurant, cafes etc. that can increase the value of a destination, transformed into controllable elements such as historical sites, events (cultural activities, festivals etc.) form an environment where “there are plenty of things to do” and can create a favourable psychological image that will make the tourist return to this destination. The transformation of these attributes into advantages for the tourist, so that a destination can be differentiated, takes places within a positioning strategy.